Lithographic Multicolor Patterning on Hybrid Perovskites for Nano‐Optoelectronic Applications. Issue 48 (26th October 2022) - Zhou, Dawei; Zhao, Peiyi; Zhang, Junran; Jiang, Xiaohong; Qin, Sichen; Zhang, Xu; Jiang, Ran; Deng, Yifan; Jiang, Hanjun; Zhan, Guixiang; Luo, Yan; Ma, Huifang; et al.
Abstract: Ultrathin hybrid perovskites, with exotic properties and two‐dimensional geometry, exhibit great potential in nanoscale optical and optoelectronic devices. However, it is still challenging for them to be compatible with high‐resolution patterning technology toward miniaturization and integration applications, as they can be readily damaged by the organic solvents used in standard lithography processes. Here, a flexible three‐step method is developed to make high‐resolution multicolor patterning on hybrid perovskite, particularly achieved on a single nanosheet. The process includes first synthesis of precursor PbI2, then e‐beam lithography and final conversion to target perovskite. The patterns with linewidth around 150 nm can be achieved, which can be applied in miniature optoelectronic devices and high‐resolution displays. As an example, the channel length of perovskite photodetectors can be down to 126 nm. Through deterministic vapor‐phase anion exchange, a perovskite nanosheet can not only gradually alter the color of the same pattern in a wide wavelength range, but also display different colors simultaneously. The authors are optimistic that the method can be applied for unlimited perovskite types and device configurations for their high‐integrated miniature applications. Abstract : High‐resolution multicolor patterning is achieved in a hybrid perovskite nanosheet, of which the linewidth can be down to ≈150 nm. A single perovskite nanosheet can not only gradually alter the color of the same pattern in a wide wavelength range, but also display different colors simultaneously. A perovskite photodetector with short channel length exhibits high responsivity.